2015
DOI: 10.1097/jnn.0000000000000117
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers of Older Persons With Multiple Sclerosis

Abstract: The challenges older caregivers face when caring for older persons with MS have been shown to affect their mental and physical QOL. Nurses who care for older patients with MS will increasingly rely on older caregivers to provide patient-centered interventions. This descriptive study, based on the Anderson theoretical model, provides insight on factors impacting older caregivers' HRQOL. Further research is necessary to elucidate the types of interventions that support them as they care for older patients with M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…For instance, challenges related to caregiving and MS were described as a compromise to carers' QoL. This supports quantitative studies showing that MS symptoms, caregiving demands, environmental and financial barriers are significant predictors of carer burden and poor QoL (Akkus, 2011;Alshubaili, Ohaeri, Awadalla, & Mabrouk, 2008;Buhse, Ratta, Galiczewski, & Eckardt, 2015;van der Hiele et al, 2019;Katsavos et al, 2017;Rivera-Navarro et al, 2009). Participants also frequently reported missing out on social activities and having poorer health due to MS caregiving which appeared to play an important role in their QoL.…”
Section: Discussionsupporting
confidence: 69%
“…For instance, challenges related to caregiving and MS were described as a compromise to carers' QoL. This supports quantitative studies showing that MS symptoms, caregiving demands, environmental and financial barriers are significant predictors of carer burden and poor QoL (Akkus, 2011;Alshubaili, Ohaeri, Awadalla, & Mabrouk, 2008;Buhse, Ratta, Galiczewski, & Eckardt, 2015;van der Hiele et al, 2019;Katsavos et al, 2017;Rivera-Navarro et al, 2009). Participants also frequently reported missing out on social activities and having poorer health due to MS caregiving which appeared to play an important role in their QoL.…”
Section: Discussionsupporting
confidence: 69%
“…Additionally, other health factors, such as number of and specifics about concurrent health condition(s), could have been included. 2 However, the health variables included in the current study have been shown to associate significantly with caregiver stress and mirror those tested in similar models. 2,7,8,10,17 Lastly, as mentioned, due to researcher error one of the six domains of the caregiver selfcare scale was not included in analyses here.…”
Section: Discussionsupporting
confidence: 56%
“…1 Unlike other neurological diseases, MS often is diagnosed in young adulthood and only minimally affects life expectancy. 2 There is no known way to predict the onset of an MS relapse, the symptoms the patient will experience, or the progression of the disease. 3 MS often leads to increasing disability, causing the individual to depend on caregivers as the disease progresses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations